Sistema de semeadura com linha dupla na cultura da soja - Dresch, Gabriel (2017)
The objective of this work was to evaluate the agronomic performance of Nidera Seeds soybean cultivar (Glycine max L.) NA 5909 RG in different row spacings and different plant populations per hectare. The spacings evaluated were 0.50m x 0.50m and 0.17m x 0.50m, the populations evaluated were 260,000, 300,000 and 340,000 plants / ha-1. A randomized complete block design (DBC) with a 2x3 factorial scheme was used, with four replications, totaling 24 plots. The simple line plots (0.5m x 0.5m) consisted of 6 lines of 10m in length with a total area of 30.0 m², having a useful area of 8 m² (two central lines of 8.0 m in length). The double line plots (0.17m x 0.5m) consisted of 8 lines of 10 m in length with a total area of 26.8 m², having a floor space of 10.72 m² (four central lines of 8.0 m of length). It was evaluated in the experiment the rate of emergence speed, Asian rust severity (Phakopsora pachyrhizie), stem diameter, thousand seed weight and productivity. The largest populations had the highest rates of emergence velocity, while the largest stem diameters were found in the lowest populations in both spacings. The highest average values of severity were found in the populations of 340.000 thousand plants / ha-1 in the normal spacing (0.5m x 0.5m) and in the populations of 300.000 and 340.000 plants / ha-1in the double row spacing (0.17m x 0.5m), not was differing between them. The mass of a thousand grains showed differences between the evaluated treatments and the highest yields were found in the normal spacing (0.5m x 0.5m) in the populations of 300.000 and 340.000 plants / ha-1 .